Digital Marketing Communication for Non-governmental Organization - I , Made Sindhu Yoga; Ramawidjaya Bumi, Handoko (International Journal of Psychosocial Rehabilitation, 2020)
This research purpose is to gather supporters and donators for the Bali WISE program through the power of content writing, content visuals, and social media. With this three-key concept, this study wants to create the perfect formula for the R.O.L.E. Foundation program, Bali WISE, so it can share the most impactful message in the content that they share. The final result is getting more donations from satisfying supporters and creating a communication path between the Bali WISE program and its supporters. This paper is also going to contribute to the social media marketing point of view on NGOs in Indonesia. Through this finding, this study tries to fill the gap from previous research provided from the first and second world countries. Indonesia has a different type of consumer and also uses a different type of social media to attract a different type of group. By finding the right content strategy formula, it is not only beneficial for the Bali WISE program itself but also for all NGOs in Indonesia who struggle to find the right formula to gain more supporters and donors from social media.